2019
DOI: 10.3390/cancers12010071
|View full text |Cite
|
Sign up to set email alerts
|

Angioregulatory microRNAs in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is one of the leading causes of cancer mortality. Angiogenesis is a rate-determining step in CRC development and metastasis. The balance of angiogenic and antiangiogenic factors is crucial in this process. Angiogenesis-related genes can be regulated post-transcriptionally by microRNAs (miRNAs) and some miRNAs have been shown to shuttle between tumor cells and the tumor microenvironment (TME). MiRNAs have context-dependent actions and can promote or suppress angiogenesis dependent on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 201 publications
0
18
0
Order By: Relevance
“…In recent decades, numerous evidence has revealed that miRNAs act as crucial players in the development of various types of human malignancies [ 38 , 39 ]. Accumulating researches have demonstrated that dysregulation of neoplasm-associated miRNAs is involved in the occurrence and development of human HCC [ 23 , 24 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, numerous evidence has revealed that miRNAs act as crucial players in the development of various types of human malignancies [ 38 , 39 ]. Accumulating researches have demonstrated that dysregulation of neoplasm-associated miRNAs is involved in the occurrence and development of human HCC [ 23 , 24 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The balance between angiogenic and anti-angiogenic factors is pivotal in the manipulation of angiogenesis. 48 Vascular endothelial growth factor A (VEGFA) and its receptors are two important factors in angiogenesis. 9 Recent researches on tumor metastasis highlighted the importance of miRNAs and angiogenesis.…”
Section: Main Textmentioning
confidence: 99%
“…MicroRNA (miRNA) are small non-coding RNA (18-25 bases) molecules that regulate gene expression at the posttranscriptional level through degradation or translational repression of a target mRNA. It has been reported that Nivolumab Checkpoint inhibitors Second line [102] deregulation of miRNAs can lead to abnormal angiogenesis, which is the hallmark of cancer [85] Table 3 summarizes the main microRNAs associated with angiogenesis in endothelial cell, pericytes, and CSC.…”
Section: Mechanism Of Regulation Of Pericytes and Cscmentioning
confidence: 99%